Feasibility of long-term NDT programme for system-wide monitoring of bridge deck condition in Indiana, USA. Issue 3 (27th July 2018) - Taylor, Benjamin; Qiao, Yu; Bowman, Mark; Labi, Samuel
Abstract : Through effective and proactive monitoring, highway agencies can acquire information needed for deck repair or replacement timing decisions. However, system-wide monitoring of infrastructure requires a large expenditure outlay and therefore needs to be justified by comparing its costs to the potential savings if such monitoring leads to timely actions. This paper presents a framework that considers two strategies for managing a bridge deck network: a condition-based strategy that involves monitoring and repair and a time-based strategy that involves repairs at specific time intervals without condition monitoring. Using a case study, the paper calculates the life-cycle cost of each strategy as the sum of the monitoring and repair costs. The paper estimates that if a non-destructive test (NDT) is used as the monitoring platform system-wide, the unit monitoring cost will be $0·04–0·35/ft 2 ($0·43–3·77/m 2 ) of deck (average $0·22/ft 2 ($2·37/m 2 )). This cost is expected to be different for other inventories due to differences in age, inventory size and bridge proximities. The paper determines that the NDT monitoring programme benefits outweigh its costs ($3·68–10·42 rate of return in repair savings for every dollar of investment in that programme). The paper also analyses the sensitivity of the outcome to key evaluation factors.